2022
DOI: 10.3390/cancers14143353
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Trastuzumab-Induced Cardiac Toxicity in HER2- Positive Breast Cancer Patient Population

Abstract: Trastuzumab-induced cardiotoxicity (TIC) can lead to early treatment discontinuation. The aim of this study was to evaluate: N-terminal brain natriuretic peptide (NT-proBNP), creatine kinase-MB (CK-MB), myoglobin, and selected biochemical and clinical factors as predictors of TIC. One hundred and thirty patients with HER2-positive BC receiving adjuvant trastuzumab therapy (TT) were enrolled. Measurement of cardiac markers and biochemical tests as well as echocardiography were performed prior to TT initiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The evaluation of these cardiac biomarkers is theoretically an important component for monitoring of patients undergoing trastuzumab chemotherapy, since they provide evidence of even subtle cardiac dysfunction, before it becomes obvious in echocardiography. Thereby, several prospective studies [ 43 , 44 , 45 , 46 , 47 ] have proposed those cardiac biomarkers, as surrogate indices of cardiotoxicity with controversial results. In our systematic review, we attempted to evaluate the impact of ACEIs/ARBs and or BBs on the aforementioned biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of these cardiac biomarkers is theoretically an important component for monitoring of patients undergoing trastuzumab chemotherapy, since they provide evidence of even subtle cardiac dysfunction, before it becomes obvious in echocardiography. Thereby, several prospective studies [ 43 , 44 , 45 , 46 , 47 ] have proposed those cardiac biomarkers, as surrogate indices of cardiotoxicity with controversial results. In our systematic review, we attempted to evaluate the impact of ACEIs/ARBs and or BBs on the aforementioned biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…The studies focusing on the role of natriuretic peptides (NPs) in predicting and/or detecting CTRCD in breast cancer patients [ 86 , 87 , 90 , 91 , 92 , 96 , 97 , 98 , 99 , 100 , 101 , 103 , 105 , 106 , 109 , 113 , 114 , 117 , 118 , 119 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], as identified in the review, are shown in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to above-mentioned biomarkers, other potentially promising biomarkers are currently under investigation for their utility in the detection and/or prediction of CTRCD including: coronary artery calcification [ 298 ], endothelin-1 [ 299 ], neuregulin-1 [ 285 , 300 ], plasma bioactive adrenomedullin (ADM) [ 301 ], fragmented QRS (fQRS) [ 302 ], D-dimer [ 303 ], soluble fms-like tyrosine kinase receptor (sFlt)-1 [ 105 ], soluble ST2 (sST2) [ 145 , 149 , 171 , 279 , 304 ], CK-MB [ 134 , 286 ], topoisomerase II α gene ( TOP2A ) [ 305 ], cardiac myosin light chain 1 (cMLC-1) [ 306 ], vascular endothelial growth factor (VEGF) [ 93 ], placental growth factor (PIGF) [ 93 , 98 ], procollagen-derived type-I C-terminal-propeptide (PICP) [ 307 ], epicardial adipose tissue (EAT) volume [ 308 , 309 ], circulating bilirubin [ 310 ], hemopexin [ 311 ], glycated hemoglobin (HbA(1)c) [ 103 ], advanced oxidation protein products (AOPP) [ 102 ], human resistin [ 312 ] and vascular adhesion molecule 1 (VCAM-1) [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is no evidence to support the use of cardiovascular biomarkers such as NT-pro BNP, CK-MB, or myoglobin to anticipate the onset of cardiovascular issues. The challenge is to treat BC effectively while limiting toxicity [ 22 ]. According to the results of the present study, non-responsive women demonstrated a higher frequency of PTEN loss compared with responsive women.…”
Section: Discussionmentioning
confidence: 99%